(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті аналізуються загальні психологічні підходи до вивчення взаємозв’язку інтелекту та творчості з метою виявлення психолого-педагогічних умов ефективного формування інтелектуальної діяльності в навчанні. Ключові слова: розвиток інтелекту, інтелектуалізація, розвиток творчості. The paper analyzes the general psychological approaches to examine the relationship between intelligence and creativity to identify psycho-pedagogical conditions for effective formation of intellectual activity in the training. Key words: development of intelligence, intellectualization, the development of creativity.